Catalogue of Egyptian, Near Eastern, Greek, Etruscan and Roman Antiquities, Islamic Pottery, African, South American, Oceanic and Indian Art. Sotheby’s Sales Catalogues. Day of Sale: Monday, 18th October, 1965 - Anonymus, A. (1965)
spez. p. 27-34, nos. 91-123: Near Eastern Antiquities (nos. 93: Tepe Giyan; 96, 100, 102, 114-116: Amlaš; 97: Tepe Sialk; 98: Hasanlu; 103, 106, 107, 108, 109, 110, 111, 112, 113, 120: Luristan).